Perencanaan Rencana Kegiatan Dan Anggaran Sekolah (RKAS) Di SMA Negeri 13 Surabaya - Anugraheni Puspita (Jurnal Bintang Pendidikan Indonesia, 2023)
RKAS is a set of school action plans that cover planning, coordinating, implementing, and monitoring teaching and learning activities in the future. From this it can be concluded that the RKAS covers all parts of budget management, from planning to accountability. The School Activity and Budget Plan (RKAS) must be designed in accordance with established procedures. The procedures are (1) taking inventory of school programs/activities for the following year; (2) compiling action programs according to their types and priorities; (3) determine the work program and program details; (4) Prepare working papers and spreadsheets, set financial goals and budgets and bring them into standard RKAS format. This preparation procedure was also carried out at SMAN 13 Surabaya. In carrying out the procedures for preparing the Activity Plan and School Budget SMAN 13 Surabaya also includes teachers and school committees to take part in the discussion process regarding the planned school activity program design. The RKAS reporting process is also important in order to uphold the principles of accountability and transparency in an educational institution. This is also done by SMAN 13 Surabaya, this school uses two reporting processes, including mandatory reporting through an application that has been provided by the government in the form of the SIPLAH and ARKAS applications. This application is intended to oversee the management and planning of learning in schools, not only that at SMAN 13 Surabaya also do manual reporting, namely reporting to the school committee.